'When they act, they speak more': strategies that encourage language production in a bilingual preschool. Issue 3 (16th March 2022) - Schwarz, Mila; Deeb, Inas; Dubiner, Deborah
ABSTRACT: The objective of two-way language programs is to promote intergroup communicative competence and cultural awareness. The purpose of the study was to explore teachers' strategies implemented to create a language-conducive classroom context. To address this purpose, we used triangulation of data sources: weekly classroom observations, video recording of teachers' reflections during periodical formal meetings; and field notes. The findings indicated the following language-conducive strategies: the classroom as a community of learners, explicit request to use Arabic, ritual repetition, teacher mediated socio-dramatic play, associative mediator and language area. These strategies brought with them a change of pedagogical approach that led to increased openness to Arabic. An analysis of teachers' critical reflections of the strategy implementation revealed that they perceived these strategies as a positive factor in the enhancement of openness to Arabic.